Central European Journal of Physics - Feng, Jonathan L.; SpringerLink (Online service) (Warsaw : Versita : Imprint: Versita, co-published with Springer.)
The CEJP publishes research and review articles, rapid and short communications comments and replies that covers the following areas of physical sciences: Acoustics Astrophysics Atomic and Molecular Physics Biological and Medical Physics Complex Networks, Socio- and Econophysics Computational Physics Condensed Matter Physics Cosmology and Gravitation Fluid Mechanics Geophysics Nanophysics Optics and Lasers Particle and Nuclear Physics Plasma Physics Statistical and Nonlinear Physics Surface Physics Theoretical and Mathematical Physics.
Keywords: Physical chemistry; Geophysics; Physics; Biophysics; Biological physics; Environmental sciences; Physics, general; Physical Chemistry; Geophysics/Geodesy.; Environmental Physics; Biological and Medical Physics, Biophysics